2008
DOI: 10.3928/1081597x-20080901-18
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking is Negatively Associated With Keratoconus

Abstract: <h4>PURPOSE</h4><p> To investigate a correlation between cigarette smoking and keratoconus.</p> <h4>METHODS</h4><p>Patients with keratoconus who were treated with corneal collagen cross-linking from June 2006 to November 2007 were asked about their smoking habits. A person smoking a minimum of two cigarettes per day for more than 1 year was classified as a smoker.</p> <h4>RESULTS</h4><p>A total of 180 patients with keratoconus (mean age 28±9 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(26 citation statements)
references
References 26 publications
4
19
1
2
Order By: Relevance
“…16 Factors that may reduce keratoconus risk include smoking, which seems to have a reduced prevalence in keratoconus patients and perhaps reduces the risk by increasing corneal collagen cross-linking. 50 Diabetic hyperglycemia may increase corneal collagen cross-linking as well, 51 and it seems that diabetic patients with keratoconus have less severe disease. 52 In reviewing the possible mechanisms of keratoconus formation associated with eye rubbing, we have discussed that epithelial trauma is a result of eye rubbing.…”
mentioning
confidence: 99%
“…16 Factors that may reduce keratoconus risk include smoking, which seems to have a reduced prevalence in keratoconus patients and perhaps reduces the risk by increasing corneal collagen cross-linking. 50 Diabetic hyperglycemia may increase corneal collagen cross-linking as well, 51 and it seems that diabetic patients with keratoconus have less severe disease. 52 In reviewing the possible mechanisms of keratoconus formation associated with eye rubbing, we have discussed that epithelial trauma is a result of eye rubbing.…”
mentioning
confidence: 99%
“…10 The authors claimed that tobacco smoking represents a source of advanced glycosylation products (AGEs), similar to diabetes mellitus. Also, in the study of Spoerl et al 9 smoking was found to be negatively associated with keratoconus due to increased cross-linking in the cornea.…”
Section: Discussionmentioning
confidence: 93%
“…Nishitsuka et al have reported that smoking is related to increased corneal thickness, and Spoerl et al proposed that cigarette smoking is negatively associated with keratokonus. 8,9 In this study, we have evaluated the anterior segment parameters and pupillary functions in heavy smokers, with optical low coherence reflectometry and a corneal-topographyaberrometer device respectively. Dry eye evaluation with Schirmer's test was also performed in these patients, and the results were compared to those in age-and gender-matched healthy control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…who underwent CXL showed lower incidence of keratoconus among smokers compared with non-smokers. 34 Cigarette smoke contains toxic substances that have been shown to increase the formation of AGEs in several tissues. 35 Furthermore, keratoconus tends to appear in patients early in life, before oxidative stress has produced significant numbers of AGE cross-links.…”
Section: Discussionmentioning
confidence: 99%